Student Perceptions of the Wattpad Application to Grow Literary Literacy in the Indonesian Language and Literature Education Study Program, University of Pekalongan - Iga Mawarni, Nabila; Setyarum, Ariesma (International Proceedings of Nusantara Raya, 2023)
This study specifically aims to describe student perceptions of the Wattpad application to foster a spirit of literary literacy in the Language and Literature Education Study Program, Pekalongan University. This research is a type of qualitative research with descriptive methods. The research subjects were PBSI study program students at Pekalongan University. Collecting research data using direct interviews with a purposive sampling technique, namely a sampling technique for data sources with certain considerations that the target is considered to know best about what is expected of the topic of a problem in research. Based on the results of the research, it is known that the Wattpad application is able to foster a spirit of literary literacy in PBSI study program students at Pekalongan University. The results of student perceptions were obtained from questions related to categories capable of supporting literary literacy skills consisting of knowledge categories, understanding categories, application categories, analysis categories, evaluation categories and creation categories. The real manifestation of cultivating a spirit of literary literacy in students of the PBSI study program at Pekalongan University includes growing interest in reading and being able to provide reference ideas to hone student writing creativity in the field of literature.